Karakteristik Penderita Diabetes Mellitus Dengan Komplikasi Yang Di Rawat Inap Di RSUD Deli Serdang Tahun 2012 - Fitriana Butarbutar; Hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Diabetes Mellitus (DM) is a group of metabolic diseases that a problem in many countries including Indonesia. According to the American Diabetes Association (2004) the number of people with diabetes in Indonesia ranked 4th largest (8.4 million people) in the world. In North Sumatra province in 2008, prevalence of DM 1.21%. DM is known as